(untitled) (Contemporary Journal of Social Science Review, 2025)
Black feminism introduces a new mode of reading and listening to trauma fiction. This article engages trauma theory through Black Literature allowing to refine and address crucial problems concerning the representation of trauma and strategies of survival amid patriarchal society. The study focuses centrally on persuasive depiction of a troubled childhood reflecting on the phenomena of abusive parenting and sexual violation resulting in psychological and emotional trauma. The conduct of the father is also examined for he not only is a perpetrator as he satisfies his lust by abusing his daughter but goes one step below by becoming a predator as he misses no chance to suppress her. This contemporary literary incest-narrative searches for causes of wounds and chaos in the life of a silenced and abused child. The narrative demonstrates how masculinity is used as a means of oppression in human interrelations along with the tragic endeavour of the protagonist who struggles to attain integrity while coping with disgrace and loneliness.